Evaluation of the Self-Help Housing Assistance Program (BRS) in Enhancing Rural Area Planning in Subulussalam Utara Village, Simpang Kiri District, Subulussalam City, Aceh Province: English - masrizal; Lubis, Satia Negara; Lubis, Arga Abdi Rafiud Darajat (Asian Multidisciplinary Research Journal of Economy and Learning, 2024)
This study evaluates the implementation of the Self-Help Housing Assistance Program (BRS) in Subulussalam Utara Village, Simpang Kiri District, Subulussalam City, Aceh Province, focusing on factors that support and hinder its success. The research aims to understand how the BRS program contributes to rural area planning and its impact on the local community, particularly low-income families needing adequate housing. Utilizing qualitative methods, the study collects data through in-depth interviews, observations, and documentation. The findings highlight the importance of effective communication and collaboration among stakeholders while identifying challenges such as limited human resources and target accuracy. Recommendations are made to enhance coordination, improve human resource capacity, and ensure the program's benefits reach the intended beneficiaries.